Otoczenie kościoła Ojców Misjonarzy - z dziejów urbanistyki Bydgoszczy 1920-1939 (Kronika Bydgoska, 2013)
In the inter-war period, the monumental Church of St Vincent de Paul was erected in Ossolińskich Avenue. The area around the church was the subject of searching planning analyses. Starting from 1927, the following projects were created: by B. Raczkowski (in 1930), A. Ballenstaedt (1930), joint project of members of the TUP Society of Polish Town Planners in Warsaw (1931), and Piotr Seidel (1934). These projects took into consideration the layout of the square in front of the church front facade, the pavement layout, the buildings in the square from the eastem and western sides, as well as the buildings in the immediate neighbourhood of the Mission Priests’ complex. The view axes, green areas, and height of planned buildings were included as well. The article is an analysis and comparison of different ideas of architects and urban planners from the period of the Second Republic of Poland. The present-day shape of the space around the basilica is the result of ideas from before 1939 and of post-war planners.